Genetic differences associated with dopamine and serotonin release mediate fear-induced bradycardia in the human brain - Simone Battaglia; Claudio Nazzi; Julian F. Thayer (Translational Psychiatry, 2024)
Abstract Fear-induced bradycardia, a transient heartbeat deceleration following exposure to threat, is a physiological index observable in humans, especially in fear conditioning experiments. While gaining interest in recent years, it is still currently underemployed in neuroscientific research compared to more popular physiological indices. Besides its use in research, it could also constitute a valuable resource in a clinical psychiatry setting, as many disorders are also characterized by altered heart rate responses. However, differences in fear-induced bradycardia may also be subtended by genetic interindividual differences, thus suggesting precaution when recommending its use in the clinical setting. Here, we discussed the first endeavors that aimed at clarifying the genetic underpinnings of heart rate variations, which suggest that individual genetic differences have a role in defining the characteristics of heart rate responses. Given this, translating heart rate measurements in the clinical setting must be implemented with caution. Future endeavors in this field will aim at identifying these differences even further, thus allowing for more precise clinical interventions.